Tissue-specific resistance and susceptibility to the tomato brown rugose fruit virus (ToBRFV) conferred by Solanum pennellii loci - Edan Rochsar; Shai Torgeman; Kfir Bandel; Amnon Koren; Chen Klap; Aviv Dombrovsky; Dani Zamir (BMC Plant Biology)
Abstract Background Plant breeding research heavily relies on wild species, which harbor valuable traits for modern agriculture. This work employed a new introgression population derived from Solanum pennellii (LA5240), a wild tomato native to Peru, composed of 1,900 genotyped backcross inbred lines (BILs_BC2S6) in the tomato inbreds LEA and TOP cultivated genetic backgrounds. This Peruvian accession was found resistant to the most threatening disease of tomatoes today, caused by the tobamovirus tomato brown rugose fruit virus (ToBRFV). Results The BILs were inoculated and genotyped for 5000 single primer enrichment technology (SPET) markers and phenotyped for virus presence, using ELISA, and for visual symptoms in the terminal shoot, axillary shoots, and fruits. Growth of the recombinant BILs in a highly infected greenhouse enabled the mapping of a quantitative trait locus (QTL) for resistance to ToBRFV to chromosome 2 next to tomato mosaic-1 (Tm-1). The QTL reduced the ELISA values and the symptoms of the axillary shoots in both TOP and LEA BILs. Another locus for resistance was mapped to chromosome 3, which protected the terminal and axillary shoots of the TOP BILs only. A strong QTL for fruit susceptibility to ToBRFV was mapped to chromosome 7 only in the LEA background. Conclusion Taken together, S. pennellii loci conferring resistance and susceptibility act in a tissue-specific manner and are modified by genetic background.